The International AIDS Vaccine Initiative (IAVI) : is it getting new science and technology to the world's neglected majority? - Chataway, Joanna (2006)
Examines public-private partnerships popularity. Describes the key characteristics of the International Aids Vaccine Initiative (IAVI) and explains why it differs from more traditional partnerships. Notes that IAVI has had some success in bringing new science and technology closer to the world's poor. Looks at how this success was achieved and the implications for theoretical and practical approaches to science and technology capacity building.